Weight Loss in Obese Prepubertal Children: The Influence of Insulin Resistance. (July 2013) - Chiavaroli, Valentina; Giannini, Cosimo; D'Adamo, Ebe; de Giorgis, Tommaso; Torello, Monica; D'Orazio, Nicolantonio; Sestili, Simona; Chiarelli, Francesco; Mohn, Angelika
<x xml:space="preserve">Abstract</x> Background. Insulin resistance (IR), a link of paramount importance between obesity and cardiovascular/metabolic complications, seems to be implicated in weight changes. Objective. To determine whether IR could influence weight status during a 1-year intervention program in obese prepubertal children. Methods. Forty-four children with IR (IR group) and 42 children without IR (NIR group) were enrolled. Body mass index standard deviation score (BMI-SDS), waist circumference (WC), and homeostasis model assessment (HOMA-IR) were evaluated. Results. NIR children showed a significant reduction of BMI-SDS and WC at final assessment (p = 0.009 and p = 0.001, respectively), whereas IR children presented unchanged values. HOMA-IR decreased after intervention in the NIR group (p = 0.0008), but was exacerbated in IR children (p = 0.004). A positive and significant association between HOMA-IR at baseline and BMI at follow-up was found (B ± SE = 0.87 ± 0.24, p = 0.001). HOMA-IR at baseline was also significantly associated with WC at follow-up (B ± SE = 2.12 ± 0.69, p = 0.003). Conclusions. IR seems to influence adiposity changes in obese prepubertal children. Further longitudinal studies are needed to verify the relationship between IR and weight loss during childhood.